Preparation method of thin-gauge high-strength Fe50Mn30Co10Cr10 high-entropy alloy

Through two-stage cold rolling technology and heat treatment process, the problem of low strength and easy cracking of Fe50Mn30Co10Cr10 high-entropy alloy when cold rolled at room temperature was solved, and the goal of preparing thin specifications and high-strength Fe50Mn30Co10Cr10 high-entropy alloy was achieved.

CN119411027APending Publication Date: 2025-02-11EAST CHINA JIAOTONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411652716.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The maximum pressure rate of Fe50Mn30Co10Cr10 high-entropy alloy is only about 60% when cold rolled at room temperature, making it difficult to prepare thin-specification products. At the same time, its strength is low and cracking is prone to occur when rolled under high pressure.

Method used

Two-stage cold rolling technology is used to combine appropriate heat treatment processes, including hot rolling, primary cold rolling, intermediate annealing, secondary cold rolling and final annealing. By regulating various process parameters, the rolling plasticity and mechanical properties of the material are improved.

Benefits of technology

A thin-specification Fe50Mn30Co10Cr10 high-entropy alloy with a thickness of 0.8 to 1.0 mm was prepared when the total cold rolling pressure rate of two stages was more than 80%, and its yield strength and tensile strength reached 600 to 690MPa and 980 to 1008MPa, with elongation maintained 34% to 37%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411027A_ABST
    Figure CN119411027A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metallurgy, and particularly relates to a preparation method of a thin-specification high-strength Fe50Mn30Co10Cr10 high-entropy alloy. Firstly, raw materials are put into a vacuum induction furnace to be smelted and cast into an as-cast plate blank; and then the as-cast plate blank is subjected to homogenization treatment and then subjected to multi-pass hot rolling, and a hot-rolled plate is obtained. And after pickling the hot-rolled plate, carrying out primary cold rolling, intermediate annealing and secondary cold rolling. And finally, the secondary cold-rolled plate is subjected to final annealing at the temperature of 650-700 DEG C, the heat preservation time is 6-10 min, air cooling is conducted to the room temperature, and a final annealing plate is obtained. According to the preparation method disclosed by the invention, the Fe50Mn30Co10Cr10 high-entropy alloy with the thin specification of 0.8-1.0 mm and coexistence of fine recrystallized grains and a deformation structure is prepared, the yield strength of the Fe50Mn30Co10Cr10 high-entropy alloy reaches 600-690 MPa, the tensile strength reaches 980-1008 MPa, and the ductility reaches 34-37%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metallurgy, and specifically relates to a thin-gauge high-strength Fe 50 Mn 30 Co 10 Cr 10 Preparation method of high entropy alloy. Background Art

[0002] In recent years, with the continuous advancement of automobile lightweight manufacturing technology, the development trend of environmental protection, energy saving and the need for higher safety, higher requirements have been placed on the strength and plasticity of automobile lightweight steel. High manganese steel has good toughness, wear resistance and low density, and the research on its strength and plasticity improvement has attracted extensive attention from researchers. 50 Mn 30 Co 10 Cr 10 (atomic ratio) High entropy alloy is a new type of material developed based on high manganese steel system in recent years. The alloy has a variety of deformation mechanisms, including dislocation slip, face-centered cubic structure (FCC) phase stacking fault, phase transformation induced plasticity (TRIP), twin induced plasticity (TWIP). It has excellent elongation (~80%), but its low yield strength (~300MPa) and tensile strength (~800MPa) limit its application. Rolling process has been widely used as a simple and economical method to produce large fine-grained materials in the form of plates and sheets. Nearly 70% of the world's metal materials need to be processed by rolling before they can be applied to industry. Rolling and subsequent annealing processes can refine grains and adjust phase composition, thereby improving mechanical properties. Therefore, rolling process plays an irreplaceable role in national economic construction and is one of the most important methods to improve material strength and organizational uniformity.

[0003] Judging from the papers and patents published so far, Fe 50 Mn 30 Co 10 Cr 10 Most of the research on high entropy alloys is focused on the casting field, and relatively few studies have been conducted on the use of rolling technology to prepare large-sized bulk materials. 50 Mn 30 Co 10 Cr 10 The cold rolling reduction rate of the alloy is generally below 60%, mainly because when the reduction rate exceeds 60%, the alloy sheet will show obvious cracking, making it difficult to make thin-gauge products, which is difficult to meet the current application needs for lightweight materials. Therefore, it is necessary to develop new rolling and heat treatment processes to achieve large-size and large-reduction Fe 50Mn 30 Co 10 Cr 10 Preparation of high entropy alloys and improving their strength at the same time. Summary of the invention

[0004] For Fe 50 Mn 30 Co 10 Cr 10 The existing high entropy alloy has problems such as low strength and cracking caused by large reduction rate rolling. The purpose of the present invention is to provide a thin-gauge high-strength Fe 50 Mn 30 Co 10 Cr 10 The preparation method of high entropy alloy is to enhance Fe by using two-stage cold rolling combined with appropriate heat treatment process. 50 Mn 30 Co 10 Cr 10 The strength and toughness of high entropy alloys.

[0005] The technical solution of the present invention is:

[0006] A thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 The preparation method of high entropy alloy is carried out according to the following steps:

[0007] (1) Casting: First, high-purity metals of Fe, Mn, Co, and Cr with a purity of more than 99.9wt% are selected as raw materials, and the atomic percentage of each element is: Fe 50%, Mn 30%, Co 10%, Cr 10%; then the mixed material is placed in a vacuum induction furnace for melting, and then cast into a cast slab with a thickness of 20 to 30 mm;

[0008] (2) Homogenization treatment: The as-cast slab is placed in a heating furnace for homogenization treatment at a holding temperature of 1200°C for 2 hours;

[0009] (3) Hot rolling: The homogenized slab is subjected to multiple hot rolling passes, with a hot rolling reduction rate of 75% to 87%, a single-pass reduction rate of 20% to 35%, a starting rolling temperature of 1100 to 1150°C, a final rolling temperature of 1000 to 1030°C, and finally water-cooled to room temperature to obtain a hot-rolled plate;

[0010] (4) Single cold rolling: After the hot-rolled plate is pickled to remove the iron oxide scale, it is rolled in multiple passes at room temperature using a four-roll mill, with a single pass reduction rate of 10% to 20% and a single cold rolling reduction rate of 50% to 60%, to obtain a single cold rolled plate;

[0011] (5) Intermediate annealing: annealing the primary cold-rolled sheet to obtain an intermediate annealed sheet, using argon as the protective gas during the annealing process; wherein the annealing temperature is 900-1050°C, the heating rate is ≥10°C / s, the holding time is 8-10 min, and then air-cooled to room temperature;

[0012] (6) Secondary cold rolling: The intermediate annealed sheet is subjected to multiple-pass rolling at room temperature using a four-roll rolling mill, with a single-pass reduction rate of 10% to 20% and a secondary cold rolling reduction rate of 50% to 60%, to obtain a secondary cold rolled sheet with a thickness of 0.8 to 1.0 mm;

[0013] (7) Final annealing: The secondary cold rolled sheet is subjected to recrystallization annealing to obtain a final annealed sheet. Argon is used as a protective gas during the annealing process. The annealing temperature is 650-700°C, the heating rate is ≥10°C / s, the holding time is 6-10 min, and the sheet is air-cooled to room temperature.

[0014] The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 The preparation method of high entropy alloy, in step (3), the hot-rolled plate structure is a two-phase structure of FCC and HCP, wherein the volume proportion of the FCC phase is 70% to 80%.

[0015] The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 The preparation method of high entropy alloy, in step (4), the single cold rolled sheet structure is a FCC and HCP dual phase structure, wherein the volume proportion of the FCC phase is 10% to 15%.

[0016] The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 The preparation method of high entropy alloy, in step (5), the intermediate annealing plate structure is completely recrystallized, has a large number of annealing twins, and the average grain size is 3.5-8.5μm; the structure is a FCC and HCP two-phase structure, wherein the volume proportion of the FCC phase is 90%-98%.

[0017] The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 The preparation method of high entropy alloy, in step (6), the secondary cold rolled sheet has a dual-phase structure of FCC and HCP, wherein the volume fraction of the FCC phase is less than 5%.

[0018] The thin gauge high strength Fe 50 Mn30 Co 10 Cr 10 The preparation method of high entropy alloy, in step (7), the final annealed plate structure is FCC single-phase structure, the recrystallization rate is 70% to 92%, and the average grain size is 1.1 to 1.4 μm.

[0019] The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 The preparation method of high entropy alloy, in step (7), the yield strength of the final annealed plate reaches 600-690MPa, the tensile strength reaches 980-1008MPa, and the elongation reaches 34%-37%.

[0020] The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 The preparation method of high entropy alloy comprises the following steps: the total reduction rate of the first cold rolling and the second cold rolling is 80% to 84%.

[0021] The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 The preparation method of the high entropy alloy comprises the following steps: the thickness of the hot-rolled plate is 4-5 mm, the thickness of the first cold-rolled plate is 1.6-2.0 mm, and the thickness of the second cold-rolled plate is 0.8-1.0 mm.

[0022] The design idea of ​​the present invention is:

[0023] Fe 50 Mn 30 Co 10 Cr 10 The maximum reduction rate of cold rolling of high entropy alloys at room temperature is about 60%, which makes it difficult to produce thin-gauge products. The two-stage cold rolling technology is used for processing. By introducing an intermediate annealing process after the first cold rolling, the strain hardening effect after rolling is eliminated, and the cracking of the material during the second cold rolling process is avoided. In the subsequent final annealing process, low-temperature annealing is used to refine the grains as much as possible while retaining a certain deformation structure to form a heterogeneous structure. Finally, under the combined effects of dislocation slip, grain refinement, TRIP, and TWIP effects, Fe 50 Mn 30 Co 10 Cr 10 The high entropy alloy achieved large plastic deformation with a total reduction rate of more than 80% in two-stage cold rolling, and produced thin-gauge products with a thickness of 0.8 to 1.0 mm, while the yield strength and tensile strength reached a high level.

[0024] Compared with the prior art, the characteristics and beneficial effects of the present invention are:

[0025] (1)Fe 50 Mn 30 Co 10 Cr 10 High entropy alloys are prone to cracking when the reduction rate exceeds 60% during room temperature rolling, and thinner materials cannot be prepared. The present invention adopts a two-stage cold rolling process with appropriate heat treatment to effectively improve the rolling plasticity of the material. When the total reduction rate of the two-stage cold rolling is more than 80% and the thickness is 0.8-1.0 mm, the plate shape is still good and there is no cracking phenomenon, which can be used to prepare thinner materials.

[0026] (2) The present invention adopts an integrated process design of hot rolling, primary cold rolling, intermediate annealing, secondary cold rolling and final annealing to 50 Mn 30 Co 10 Cr 10 The structure, size and phase transformation behavior of the deformation and heat treatment organization of the high entropy alloy are effectively regulated, thereby obtaining a heterogeneous structure in which ultrafine FCC recrystallized grains and deformation structures coexist, providing an organizational basis for improving strength.

[0027] (3) Fe involved in the present invention 50 Mn 30 Co 10 Cr 10 The yield strength of the high-entropy alloy reaches up to 689MPa, the tensile strength reaches up to 1008MPa, and the elongation remains at 35.4%. It has high strength and good elongation at the same time, and has very excellent comprehensive mechanical properties.

[0028] (4) The present invention does not add other precious alloy strengthening elements, but adopts the traditional rolling and heat treatment process optimization route, has low production cost, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Fe prepared in Example 1 of the present invention 50 Mn 30 Co 10 Cr 10 Microstructure of high entropy alloy hot rolled plate.

[0030] Figure 2 Fe prepared in Example 1 of the present invention 50 Mn 30 Co 10 Cr 10 Single cold rolling structure of high entropy alloy.

[0031] Figure 3 Fe prepared in Example 1 of the present invention50 Mn 30 Co 10 Cr 10 Intermediate annealing structure of high entropy alloy.

[0032] Figure 4 Fe prepared in Example 1 of the present invention 50 Mn 30 Co 10 Cr 10 Morphology of high entropy alloy secondary cold rolled sheet.

[0033] Figure 5 Fe prepared in Example 1 of the present invention 50 Mn 30 Co 10 Cr 10 Secondary cold rolling structure of high entropy alloy.

[0034] Figure 6 Fe prepared in Example 1 of the present invention 50 Mn 30 Co 10 Cr 10 Final annealed structure of high entropy alloy.

[0035] Figure 7 Fe prepared in Example 1 of the present invention 50 Mn 30 Co 10 Cr 10 Tensile curve of high entropy alloy annealed sheet. In the figure, the horizontal axis Engineering strain is the engineering strain (%), and the vertical axis Engineering stress is the engineering stress (MPa).

[0036] Figure 8 Fe prepared in Comparative Example 1 of the present invention 50 Mn 30 Co 10 Cr 10 Macroscopic morphology of high entropy alloy secondary cold rolled sheet. DETAILED DESCRIPTION

[0037] In the specific implementation process, the present invention proposes a thin-gauge high-strength Fe 50 Mn 30 Co 10 Cr 10The preparation method of high entropy alloy is as follows: first, according to the atomic percentage of elements: Fe 50%, Mn 30%, Co 10%, Cr 10%, the raw materials are melted in a vacuum induction furnace and cast into a 20-30 mm thick cast slab. Then the cast slab is homogenized at 1200°C for 2 hours, and then hot rolled with multiple passes at a reduction rate of 75% to 87%. After pickling, the hot-rolled plate is cold rolled once, with a single pass reduction rate of 10% to 20%. Then, intermediate annealing is performed at 900-1050°C for 8-10 minutes; then, secondary cold rolling is performed to 0.8 mm, with a single pass reduction rate of 10% to 20%. Finally, the secondary cold rolled plate is kept at 650-700°C for 6-10 minutes for final annealing, and air-cooled to room temperature to obtain the final annealed plate. Thus, by controlling the hot rolling temperature, cooling method, annealing temperature, holding time and other parameters, high-strength thin-gauge Fe 50 Mn 30 Co 10 Cr 10 High entropy alloy sheet.

[0038] In the embodiment of the present invention, the electron backscatter diffraction (EBSD) system of Zeiss Gemini-300 field emission electron microscope is used to observe the material structure, and the mechanical properties are tested using a SHIMADZU AGS-X universal tensile machine.

[0039] Below, the present invention is further described in detail by examples and comparative examples. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] First, high-purity metals of Fe, Mn, Co, and Cr with a purity of more than 99.9wt% are selected as raw materials. According to the atomic percentage of the elements: Fe 50%, Mn 30%, Co 10%, Cr 10%, they are placed in a vacuum induction furnace for smelting and cast into 30mm thick cast slabs. Then the cast slabs are homogenized at 1200℃ for 2h. After that, multiple hot rolling passes with a reduction rate of about 83% are carried out (the thickness after each hot rolling pass is 20mm, 15mm, 10mm, 7mm, and 5mm, respectively) to obtain 5mm thick hot-rolled plates. The hot rolling start temperature is 1100℃, and the final rolling temperature is 1000℃. After the hot-rolled plate is pickled, the first cold rolling is carried out at room temperature using a four-roll mill for multiple passes to a thickness of 2mm (the thickness after each cold rolling is 4.0mm, 3.5mm, 3.0mm, 2.6mm, 2.3mm, and 2.0mm, respectively). Then, intermediate annealing is carried out at 1000°C, with a heating rate of 50°C / s, a holding time of 10min, and air cooling to room temperature. Subsequently, the secondary cold rolling is carried out at room temperature using a four-roll mill for multiple passes to a thickness of 0.8mm (the thickness after each cold rolling is 1.7mm, 1.5mm, 1.2mm, 1.0mm, 0.9mm, and 0.8mm, respectively). Finally, the secondary cold-rolled plate is finally annealed at 650°C, with a heating rate of 10°C / s, a holding time of 10min, and air cooling to room temperature to obtain the final annealed plate.

[0042] like Figure 1 As shown, the hot rolled plate structure of this embodiment is a FCC / HCP dual-phase structure, wherein the volume ratio of the FCC phase is 73.1%. Figure 2 As shown, the structure of the first cold-rolled sheet in this embodiment is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 12.5%. Figure 3 As shown in the figure, the structure of the intermediate annealed sheet is a FCC / HCP dual-phase structure, in which the volume proportion of the FCC phase is about 92%. The structure of the intermediate annealed sheet is completely recrystallized, with a large number of annealing twins, and the average grain size is 8.5μm. Figure 4 As shown in the figure, the morphology of the secondary cold rolled sheet shows that the material has a good shape and no cracks. Figure 5 As shown in Figure 1, the secondary cold rolling microstructure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 4.5%. Figure 6 As shown in Figure 1, the final annealed sheet structure is FCC single-phase structure, with a recrystallization rate of 75.9% and an average grain size of 1.4 μm. Figure 7 As shown, from the tensile curve of the final annealed plate, it can be seen that its yield strength and tensile strength are 609.8MPa and 984.9MPa respectively, and the elongation is 35.2%.

[0043] Example 2

[0044] High-purity metals of Fe, Mn, Co, and Cr with a purity of more than 99.9wt% are selected as raw materials. According to the atomic percentage of the elements: Fe 50%, Mn 30%, Co 10%, Cr 10%, they are placed in a vacuum induction furnace for smelting and cast into 30mm thick cast slabs. The cast slabs are then homogenized at 1200℃ for 2h. After that, multiple hot rolling passes with a reduction rate of about 83% are carried out (the thickness after each hot rolling pass is 20mm, 15mm, 10mm, 7mm, and 5mm, respectively) to obtain 5mm thick hot-rolled plates. The hot rolling start temperature is 1150℃, and the final rolling temperature is 1030℃. After the hot-rolled plate is pickled, the first cold rolling is carried out at room temperature using a four-roll mill for multiple passes to a thickness of 2mm (the thickness after each cold rolling is 4.0mm, 3.5mm, 3.0mm, 2.6mm, 2.3mm, and 2.0mm, respectively). Then, intermediate annealing is carried out at 900°C, with a heating rate of 30°C / s, a holding time of 10min, and air cooling to room temperature. Subsequently, the secondary cold rolling is carried out at room temperature using a four-roll mill for multiple passes to a thickness of 0.8mm (the thickness after each cold rolling is 1.7mm, 1.5mm, 1.2mm, 1.0mm, 0.9mm, and 0.8mm, respectively). Finally, the secondary cold-rolled plate is finally annealed at 650°C, with a heating rate of 10°C / s, a holding time of 10min, and air cooling to room temperature to obtain the final annealed plate.

[0045] The hot-rolled plate structure of this embodiment is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 79%. The first cold-rolled plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 10.3%. The intermediate annealed plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 96%. The intermediate annealed plate structure is completely recrystallized, with a large number of annealing twins, and the average grain size is 3.5μm. The secondary cold-rolled plate has a good shape and a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 4%. The final annealed plate structure is a FCC single-phase structure, with a recrystallization rate of 91.7% and an average grain size of 1.1μm. The yield strength and tensile strength of the annealed plate are 689.4MPa and 1007.9MPa, respectively, and the elongation is 34.6%.

[0046] Example 3

[0047] High-purity metals of Fe, Mn, Co, and Cr with a purity of more than 99.9wt% are selected as raw materials. According to the atomic percentage of the elements: Fe 50%, Mn 30%, Co 10%, Cr 10%, they are placed in a vacuum induction furnace for smelting and cast into a 30mm thick cast slab. The cast slab is then homogenized at 1200℃ for 2h. After that, multiple hot rolling with a reduction rate of about 86% is carried out (the thickness after each hot rolling is 20mm, 13mm, 9mm, 6mm, and 4mm, respectively) to obtain a 4mm thick hot-rolled plate. The hot rolling start temperature is 1150℃, and the final rolling temperature is 1030℃. After the hot-rolled plate is pickled, it is cold-rolled at room temperature using a four-roll mill for multiple passes to a thickness of 2mm (the thickness after each cold rolling is 3.5mm, 3.0mm, 2.6mm, 2.3mm, and 2.0mm, respectively). Then, intermediate annealing was performed at 950°C, with a heating rate of 25°C / s, a holding time of 10 minutes, and air cooling to room temperature. Subsequently, secondary cold rolling was performed using a four-roll rolling mill at room temperature for multiple passes to a thickness of 0.8mm (the thickness after each cold rolling pass was 1.7mm, 1.5mm, 1.2mm, 1.0mm, 0.9mm, and 0.8mm, respectively). Finally, the secondary cold-rolled sheet was subjected to final annealing at 680°C, with a heating rate of 20°C / s, a holding time of 8 minutes, and air cooling to room temperature to obtain the final annealed sheet.

[0048] The hot-rolled plate structure of this embodiment is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 79%. The first cold-rolled plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 10.3%. The intermediate annealed plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 91%. The intermediate annealed plate structure is completely recrystallized, with a large number of annealing twins, and the average grain size is 4.2μm. The secondary cold-rolled plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 4.5%. The final annealed plate structure is a FCC single-phase structure, with a recrystallization rate of 84.1% and an average grain size of 1.18μm. The yield strength and tensile strength of the annealed plate are 678.4MPa and 1002.3MPa, respectively, and the elongation is 34.2%.

[0049] Example 4

[0050] High-purity metals of Fe, Mn, Co, and Cr with a purity of more than 99.9wt% are selected as raw materials. According to the atomic percentage of the elements: Fe 50%, Mn 30%, Co 10%, Cr 10%, they are placed in a vacuum induction furnace for smelting and cast into 20mm thick cast slabs. Then the cast slabs are homogenized at 1200℃ for 2h. After that, multiple hot rolling passes with a reduction rate of 75% are carried out (the thickness after each hot rolling pass is 15mm, 10mm, 7mm, 5.5mm, 5mm, respectively) to obtain 5mm thick hot-rolled plates. The hot rolling start temperature is 1100℃, and the final rolling temperature is 1030℃. After the hot-rolled plate is pickled, the first cold rolling is carried out at room temperature using a four-roll mill for multiple passes to a thickness of 2.0 mm (the thickness after each cold rolling is 4.0 mm, 3.5 mm, 3 mm, 2.6 mm, 2.3 mm, and 2.0 mm, respectively). Then, intermediate annealing is carried out at 1050°C, with a heating rate of 30°C / s, a holding time of 8 minutes, and air cooling to room temperature. Subsequently, the secondary cold rolling is carried out at room temperature using a four-roll mill for multiple passes to a thickness of 1.0 mm (the thickness after each cold rolling is 1.7 mm, 1.5 mm, 1.3 mm, 1.15 mm, and 1.0 mm, respectively). Finally, the secondary cold-rolled plate is finally annealed at 700°C, with a heating rate of 35°C / s, a holding time of 6 minutes, and air cooling to room temperature to obtain the final annealed plate.

[0051] The hot-rolled plate structure of this embodiment is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 76%. The first cold-rolled plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 13%. The intermediate annealed plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 92%. The intermediate annealed plate structure is completely recrystallized, with a large number of annealing twins, and the average grain size is 7.7μm. The secondary cold-rolled plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 4.3%. The final annealed plate structure is a FCC single-phase structure, with a recrystallization rate of 90.5% and an average grain size of 1.3μm. The yield strength and tensile strength of the annealed plate are 680.3MPa and 994.6MPa, respectively, and the elongation is 35.1%.

[0052] Example 5

[0053] High-purity metals of Fe, Mn, Co, and Cr with a purity of more than 99.9wt% are selected as raw materials. According to the atomic percentage of the elements: Fe 50%, Mn 30%, Co 10%, Cr 10%, they are placed in a vacuum induction furnace for smelting and cast into 20mm thick cast slabs. The cast slabs are then homogenized at 1200℃ for 2h. After that, multiple hot rolling passes with a reduction rate of 80% are carried out (the thickness after each hot rolling pass is 15mm, 10mm, 7mm, 5mm, and 4mm, respectively) to obtain 4mm thick hot-rolled plates. The hot rolling start temperature is 1100℃, and the final rolling temperature is 1000℃. After the hot-rolled plate is pickled, the first cold rolling is performed at room temperature using a four-roll mill for multiple passes to a thickness of 1.6 mm (the thickness after each cold rolling is 3.5 mm, 3.0 mm, 2.6 mm, 2.3 mm, 2.0 mm, 1.8 mm, and 1.6 mm, respectively). Then, intermediate annealing is performed at 950°C, with a heating rate of 25°C / s, a holding time of 10 min, and air cooling to room temperature. Subsequently, the secondary cold rolling is performed at room temperature using a four-roll mill for multiple passes to a thickness of 0.8 mm (the thickness after each cold rolling is 1.4 mm, 1.2 mm, 1.0 mm, 0.9 mm, and 0.8 mm, respectively). Finally, the secondary cold-rolled plate is finally annealed at 680°C, with a heating rate of 40°C / s, a holding time of 10 min, and air cooling to room temperature to obtain the final annealed plate.

[0054] The hot-rolled plate structure of this embodiment is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 73%. The first cold-rolled plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 12.5%. The intermediate annealed plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 90.7%. The intermediate annealed plate structure is completely recrystallized, with a large number of annealing twins, and the average grain size is 4.3μm. The secondary cold-rolled plate structure is a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 4.8%. The final annealed plate structure is a FCC single-phase structure, with a recrystallization rate of 91.7% and an average grain size of 1.2μm. The yield strength and tensile strength of the annealed plate are 664.5MPa and 988.6MPa, respectively, and the elongation is 36.3%.

[0055] Comparative Example 1

[0056] First, high-purity metals of Fe, Mn, Co, and Cr with a purity greater than 99.9wt% are selected as raw materials. According to the atomic percentage of the elements: Fe 50%, Mn 30%, Co 10%, Cr 10%, they are placed in a vacuum induction furnace for smelting and cast into a 30mm thick cast slab. The cast slab is then homogenized at 1200℃ for 2h. After that, multiple hot rolling with a reduction rate of about 83% is carried out (the thickness after each hot rolling is 20mm, 15mm, 10mm, 7mm, and 5mm, respectively) to obtain a 5mm thick hot-rolled plate. The hot rolling start temperature is 1100℃, and the final rolling temperature is 1000℃. After the hot-rolled plate is pickled, it is cold-rolled at room temperature using a four-roll mill for multiple passes to a thickness of 2mm (the thickness after each cold rolling is 4.0mm, 3.5mm, 3mm, 2.5mm, 2.2mm, and 2mm, respectively). Then, intermediate annealing was performed at 700°C, with a heating rate of 10°C / s, a holding time of 10 minutes, and air cooling to room temperature. Subsequently, secondary cold rolling was performed using a four-roll rolling mill at room temperature for multiple passes to a thickness of 0.8 mm (the thickness after each cold rolling pass was 1.7 mm, 1.5 mm, 1.2 mm, 1.0 mm, 0.9 mm, and 0.8 mm, respectively). Finally, the secondary cold-rolled sheet was subjected to final annealing at 650°C, with a heating rate of 10°C / s, a holding time of 10 minutes, and air cooling to room temperature to obtain the final annealed sheet.

[0057] like Figure 8 As shown in the figure, it can be seen from the morphology of the secondary cold-rolled sheet in this comparative example that one end of the material has cracked due to the pressure, showing a transverse crack. The preparation process at this time obviously cannot protect the sheet shape well, and it is impossible to prepare thin-gauge Fe 50 Mn 30 Co 10 Cr 10 High entropy alloy.

[0058] Comparative Example 2

[0059] First, high-purity metals of Fe, Mn, Co, and Cr with a purity greater than 99.9wt% are selected as raw materials. According to the atomic percentage of the elements: Fe 50%, Mn 30%, Co 10%, Cr 10%, they are placed in a vacuum induction furnace for smelting and cast into a 30mm thick cast slab. The cast slab is then homogenized at 1200℃ for 2h. After that, multiple hot rolling with a reduction rate of about 83% is carried out (the thickness after each hot rolling is 20mm, 15mm, 10mm, 7mm, and 5mm, respectively) to obtain a 5mm thick hot-rolled plate. The hot rolling start temperature is 1100℃, and the final rolling temperature is 1000℃. After the hot-rolled plate is pickled, it is cold-rolled at room temperature using a four-roll mill for multiple passes to a thickness of 2mm (the thickness after each cold rolling is 4.0mm, 3.5mm, 3mm, 2.5mm, 2.2mm, and 2mm, respectively). Then, intermediate annealing was performed at 950°C, with a heating rate of 25°C / s, a holding time of 10 minutes, and air cooling to room temperature. Subsequently, secondary cold rolling was performed using a four-roll mill at room temperature for multiple passes to a thickness of 0.8 mm (the thickness after each cold rolling pass was 1.7 mm, 1.5 mm, 1.2 mm, 1.0 mm, 0.9 mm, and 0.8 mm, respectively). Finally, the secondary cold-rolled sheet was subjected to final annealing at 900°C, with a heating rate of 30°C / s, a holding time of 10 minutes, and air cooling to room temperature to obtain the final annealed sheet.

[0060] The secondary cold rolled sheet in this comparative example has a FCC / HCP dual-phase structure, in which the volume ratio of the FCC phase is 4.8%. The final annealed sheet has a FCC single-phase structure, which has been fully recrystallized, and the average grain size is about 4.1 μm. The yield strength and tensile strength of the annealed sheet are 334.8 MPa and 827.6 MPa, respectively, and the elongation is 48.3%, which is significantly lower than the strength in Examples 1 to 5 of this scheme.

[0061] The implementation results show that the present invention adopts a two-stage cold rolling process. By introducing an intermediate annealing process after the first cold rolling, the strain hardening effect after rolling is eliminated, and the cracking of the material during the second cold rolling process is avoided. By optimizing the final annealing process, a heterogeneous structure with fine recrystallized grains and partially deformed structures is obtained, and the yield strength and tensile strength are improved by the combined effect of multiple strengthening mechanisms, while maintaining good elongation. Finally, when the two-stage cold rolling reduction rate is more than 80%, a thin-gauge Fe with good plate shape is prepared. 50 Mn 30 Co 10 Cr 10 High entropy alloy and maintain high strength.

Claims

1. A thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 A method for preparing a high entropy alloy, characterized in that: Follow these steps: (1) Casting: First, high-purity metals of Fe, Mn, Co, and Cr with a purity of more than 99.9wt% are selected as raw materials, and the atomic percentage of each element is: Fe 50%, Mn 30%, Co 10%, Cr 10%; then the mixed material is placed in a vacuum induction furnace for melting, and then cast into a cast slab with a thickness of 20 to 30 mm; (2) Homogenization treatment: The as-cast slab is placed in a heating furnace for homogenization treatment at a holding temperature of 1200°C for 2 hours; (3) Hot rolling: The homogenized slab is subjected to multiple hot rolling passes, with a hot rolling reduction rate of 75% to 87%, a single-pass reduction rate of 20% to 35%, a starting rolling temperature of 1100 to 1150°C, a final rolling temperature of 1000 to 1030°C, and finally water-cooled to room temperature to obtain a hot-rolled plate; (4) Single cold rolling: After the hot-rolled plate is pickled to remove the iron oxide scale, it is rolled in multiple passes at room temperature using a four-roll mill, with a single pass reduction rate of 10% to 20% and a single cold rolling reduction rate of 50% to 60%, to obtain a single cold rolled plate; (5) Intermediate annealing: annealing the primary cold-rolled sheet to obtain an intermediate annealed sheet, using argon as the protective gas during the annealing process; wherein the annealing temperature is 900-1050°C, the heating rate is ≥10°C / s, the holding time is 8-10 min, and then air-cooled to room temperature; (6) Secondary cold rolling: The intermediate annealed sheet is subjected to multiple-pass rolling at room temperature using a four-roll rolling mill, with a single-pass reduction rate of 10% to 20% and a secondary cold rolling reduction rate of 50% to 60%, to obtain a secondary cold rolled sheet with a thickness of 0.8 to 1.0 mm; (7) Final annealing: The secondary cold rolled sheet is subjected to recrystallization annealing to obtain a final annealed sheet. Argon is used as a protective gas during the annealing process. The annealing temperature is 650-700°C, the heating rate is ≥10°C / s, the holding time is 6-10 min, and the sheet is air-cooled to room temperature.

2. The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 A method for preparing a high entropy alloy, characterized in that: In step (3), the hot-rolled plate has a dual-phase structure of FCC and HCP, wherein the volume proportion of the FCC phase is 70% to 80%.

3. The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 A method for preparing a high entropy alloy, characterized in that: In step (4), the microstructure of the primary cold-rolled sheet is a dual-phase structure of FCC and HCP, wherein the volume proportion of the FCC phase is 10% to 15%.

4. The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 A method for preparing a high entropy alloy, characterized in that: In step (5), the intermediate annealed sheet structure is completely recrystallized, has a large number of annealing twins, and an average grain size of 3.5 to 8.5 μm; The organization is a two-phase structure of FCC and HCP, in which the volume proportion of the FCC phase is 90% to 98%.

5. The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 A method for preparing a high entropy alloy, characterized in that: In step (6), the microstructure of the secondary cold-rolled sheet is a dual-phase structure of FCC and HCP, wherein the volume fraction of the FCC phase is less than 5%.

6. The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 A method for preparing a high entropy alloy, characterized in that: In step (7), the final annealed sheet structure is an FCC single-phase structure, the recrystallization rate is 70% to 92%, and the average grain size is 1.1 to 1.4 μm.

7. The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 A method for preparing a high entropy alloy, characterized in that: In step (7), the yield strength of the final annealed sheet reaches 600-690 MPa, the tensile strength reaches 980-1008 MPa, and the elongation reaches 34%-37%.

8. The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 A method for preparing a high entropy alloy, characterized in that: The total reduction ratio of the first cold rolling and the second cold rolling is 80% to 84%.

9. The thin gauge high strength Fe 50 Mn 30 Co 10 Cr 10 A method for preparing a high entropy alloy, characterized in that: The thickness of the hot-rolled plate is 4 to 5 mm, the thickness of the once cold-rolled plate is 1.6 to 2.0 mm, and the thickness of the twice cold-rolled plate is 0.8 to 1.0 mm.